ANALISIS PENERAPAN PSAK 65 DAN RELEVANSINYA TERHADAP PSAK 15 DAN PSAK 22 DALAM LAPORAN KEUANGAN KONSOLIDASI PT BANK MANDIRI (PERSERO) TBK TAHUN 2024 - Yunita Kusumaningrum; Tiara Ayu Wardani; Diana Fitriyani Putri; Amelia Eka Diyanti; Endang Kartini Panggiarti (Jurnal Ilmiah Akuntansi, 2026)
Thisl study aimsl to lanalyze the limplementation of PSAK 65, PSAK 15, and lPSAK 22 in lthe preparation of lconsolidated financial lstatements of lPT Bank Mandiri (Persero) Tbk. This lresearch is lqualitative and descriptive, lwith data lcollection techniques lusing documentation methods on lthe company's consolidated financial reports, annual reports, and other official documents during the reporting period of 2024. The analysis results indicate that the company has consistently applied PSAK 65 in consolidating all controlled subsidiary entities with ownership above 50%. The applicationl of PSAK 15 lhas also been lcarried out by the company inl recording investments in associate entities using the equity method after PT Bank Mandiri (Persero) Tbk acquired a 20% stake in PT Asuransi Inhealth Indonesia. The recognition and impairment testing of goodwill arising from business combinations have lbeen in laccordance with lPSAK 22. It lcan be lconcluded that lthe implementation lof these three standards ensures lthat the lconsolidated financial lstatements of lBank Mandiri (lPersero) Tbk lare prepared transparently, accurately, and lin accordance lwith generally laccepted accounting lprinciples, thus providing la comprehensive picture lof the group's lfinancial position and financial performance.